Application of the Search, Solve, Create, and Share (SSCS) Learning Model to Improve Students' Understanding of Concepts in Class XI MIPA SMAN 7 Pekanbaru - Fitri Ramadani; Susilawati Susilawati; Herdini Herdini (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to determine the improvement and category of improvement in students' understanding of the concept of buffer solutions by applying the Search, Solve, Create, and Share (SSCS) learning model. The form of this study is an experimental research with a Randomized Control Group Pretest-Posttest design. The population of this study is all students of class XI MIPA SMAN 7 Pekanbaru for the 2024/2025 school year. The research sample was students in class XI MIPA 1 as an experimental class and students in class XI MIPA 2 as a control class. The experimental class was given the treatment of the application of the SSCS learning model, while the control class was given learning without the SSCS model. The results of the data hypothesis test analysis technique used the right-hand t-test. Based on the analysis of research data, it was obtained that the tcount of 2.07 was greater than the ttable of 1.67 (dk = 67, α = 0.05) with the category of increasing students' understanding of concepts of 0.74 in the high category. The results of the study show that the Search, Solve, Create, and Share (SSCS) learning model can improve students' understanding of the concept of buffer solutions in class XI MIPA SMAN 7 Pekanbaru.